PTH-349 Use of methylene blue to identify ureters under fluorescence during laparoscopic and open colorectal surgery. (22nd June 2015) - Yeung, T; Volpi, D; Nicholson, G; Buchs, N; Cunningham, C; Guy, R; Hompes, R; Lindsey, I; George, B; Jones, O; Vojnovic, B; Hamdy, F; et al.
Abstract : Introduction: Iatrogenic ureteric injury is a serious complication of colorectal surgery. Fluorescence image guided surgery (FIGS) is an expanding field and can potentially make operations safer for patients and prevent inadvertent ureteric injury. Intravenously administered methylene blue is excreted renally and concentrated in the urine. It is fluorescent at 660nm and can therefore be used to locate ureters intraoperatively using fluorescence enabled cameras and laparoscopes. The aim of this study is to assess the use of methylene blue under fluorescence to identify ureters during laparoscopic and open colorectal surgery. The primary objective is to compare ureter identification using white light versus fluorescence in each patient. The secondary objectives are to quantify the level of fluorescence at different time points following administration of methylene blue and to work out the optimum time to visualise the ureters. Method: All adult patients undergoing either laparoscopic or open colorectal surgery were considered for inclusion into this study. Exclusion criteria were pregnancy, significant renal or hepatic impairment, and patients taking SSRIs with a risk of developing serotonin syndrome. Between 0.25 – 1 mg/kg of methylene blue was administered intravenously during the operation. Background and peak fluorescence were measured at multiple time points during the procedure, using custom-made fluorescence-enabled laparoscopes and open cameras that could detect fluorescence at 660 nm. Results: 8 consecutive patients undergoing colorectal surgery were recruited into this study, of which 6 were laparoscopic and 2 were open procedures. Out of 11 ureters, 10 were successfully visualised under fluorescence (example shown in image below). The mean time to peak fluorescence was 14.5 min after intravenous methylene blue injection. There was a low background signal, and the mean signal to background ratio was 2.74. Fluorescence could be detected up to 75 min after injection. This technique was considered useful in 4 patients: in one case, the ureter was more medial than initially thought, in another case, the ureter was not seen on white light but was seen under fluorescence, and in two cases, the ureters were traced from the pelvic brim all the way to the kidneys. There were no complications after administration of methylene blue. Conclusion: The use of methylene blue is a safe and simple technique to identify the location of ureters under fluorescence. Larger clinical studies are required to identify which subsets of patients would benefit from this form of fluorescence image guided surgery. Disclosure of interest: None Declared.